Diagnostic value of HRCT-Thorax for pandemic COVID-19 pneumonia in Pakistan - Abdul Rasheed Qureshi ,Zaheer Akhtar ,Muhammad Irfan ,Muhammad Sajid ,Zeeshan Ashraf (Journal of Rawalpindi Medical College, 2020)
Background: In the scenario of, inadequate testing, the low sensitivity of the COVID-19-PCR test, limited availability of testing kits, and low detection rate, we aimed to investigate the usefulness of high-resolution computed tomography of chest (HRCT) for diagnosing pandemic coronavirus (COVID-19) pneumonia. Objective: To determine the diagnostic efficacy of HRCT thorax in Covid-19 pandemic pneumonia. Materials and Methods: This prospective, cross-sectional study was conducted in the Pulmonology–OPD of Gulab Devi Teaching Hospital, Lahore-Pakistan from 01-04-2020 to 15-07-2020. 121 patients with dry cough, fever, and dyspnea of sudden onset were included while patients with Bronchial Asthma, ILD, Tuberculosis, Bronchiectasis, COPD, and overt heart failure were excluded. Patients were investigated with chest x-ray, HRCT, COVID-PCR, and hematological tests. HRCT films were evaluated by a qualified and experienced radiologist. Findings were summarized, organized and statistical analysis was done by using SPSS-26 software to make an inference. Results: Five patients were diagnosed as non-covid. Out of 116-diagnosed covid-19 patients, 38(32.75%) showed sub-pleural consolidation, 19(16.37%) consolidation with air-bronchogram, 29(25.0%) crazy paving sign, one pleural effusion (0.86%) and 18 cases (15.51%) displayed reticulations. 11cases(9.48%) had isolated ground glass appearances, while all categories showed it to variable extent. 65 patients (56.03%) were PCR-positive while 51(43.96) patients with positive-HRCT findings for COVID-19 pneumonia had negative nasopharyngeal-PCR. HRCT-Thorax revealed sensitivity: 97.41 %, specificity: 80%, PPV: 99.12%, NPV: 57.14%, and diagnostic accuracy of 96.69% for COVID-19 pneumonia. Conclusion: HRCT-Thorax, having high sensitivity and adequate specificity, can provide foundations for evidence-based early diagnosis and quantification of coronavirus pneumonia. It can be tremendously useful for decision making in PCR-negative patients and anticipating respiratory improvement or decline by serial scans.